THE Hubungan Kekuatan Otot Lengan Dan Otot Tungkai Dengan Kecepatan 50 Meter Bifins - Ibnu Juarsa, Aryawangsa (Jumper: Jurnal Mahasiswa Pendidikan Olahraga, 2024)
This research aims to : 1) Explains the connection between arm muscle strength and speed of 50 bifins. 2)Explains the connection of stump muscle stength and speed of 50 bifins. 3)Then the connection between arm and stump muscle strength to speed of 50 bifins. This research uses quantitative methods with correlation studies. This research is correlational which aims to find out the connection between variables. The sampling technique was carried out by using the purposive sampling method, many as 12 people. The instrument test this research is pul dynamometer test to measure arm muscle strength 2) leg dynamometer test to measure leg muscle strength 3) 50 meter bifins test to measure speed 50 meter bifins. The analysis technique used is the r analysis test. 1) There is a ngative connectionn between arm muscle strength and the speed of 50 bifins with a correlation coefficient of 0.630 r calculated (0.630) r >table (0.497 ). 2) There is a ngative connectionn between leg muscle strength and the speed of 50 bifins with a correlation coefficient of 0.692 r calculated (0.692) r >table (0.497). 3) There is connection between the arm muscle strength and stump muscle at a speed of 50 m bifins with correlation coefficient of 0,720.this shows that F calculate (4,446) > F table (4,256).